Prevalence of dementia, heart disease and stroke in community-dwelling adults in Canada, 2016-2021: opportunities for joint prevention - Sarah S. Singh; Shiran Zhong; Kem A. Rogers; Vladimir C. Hachinski; Stephanie J. Frisbee (BMC, 2023)
Abstract Introduction This aim of this study is to provide updated estimates on the prevalence of dementia, heart disease, and stroke in Canadian communities. Targeting all three conditions together, at the community level, may be key to disease prevention and health aging in the Canadian population. Methods Using nationwide health survey data, we calculated the age-standardized prevalence of self-reported dementia, heart disease and stroke in adults aged 18 years and over residing in Canadian communities from 2016 to 2021. Poisson regression models were used to detect statistically significant changes in the prevalence of all three conditions from 2016 to 2021. Results Less than 1% (~ 175,000 individuals) of adults residing in Canadian communities reported dementia, 5% (~ 1.5 million individuals) reported heart disease, and more than 1% (~ 370,000 individuals) reported stroke annually from 2016 to 2021. Overall, the age-standardized prevalence for stroke decreased minimally from 2016 to 2021 (p = 0.0004). Although the age-standardized prevalence of heart disease and dementia decreased from 2016 to 2018, subsequent increases in prevalence from 2018 to 2021 led to a lack of overall statistically significant changes from 2016 to 2021 (p = 0.10 for heart disease and p = 0.37 for dementia). Conclusion Recent increases in the prevalence of dementia, heart disease and stroke in Canadian communities threaten to reverse any gains in vascular disease prevention over the past six years. Findings reveal the urgent need for intensified prevention efforts that are community-based with a focus on joint reduction in the shared risk factors contributing to all three diseases.